Removal of heavy metal using sequencing batch reactor (SBR) - Muhammad Syafiq, Mohd Shafei (2017)
and environmental friendly methods is essential. One of the attractive methods is by using biological approach. In highlight to that, this study is conducted with the main objective is to investigate and evaluate the feasibility of removing heavy metals (Zinc and Copper) in wastewater by using indigenous microorganisms in a sequencing batch reactor (SBR). Such microorganisms could be possibly found in activated sludge from palm oil mill pond in which utilized as inoculum in this study. Prior to the experimental work, SBR was inoculated with activated sludge. Then, SBR was fed with synthetic wastewater containing Zinc and Copper at certain concentrations. The presence of the metals was determined by using Atomic Absorption Spectrometry (AAS). In addition, the variation of pH between 2 and 9 was experimented to evaluate the efficiency of the removal in response to the pH changes. As a result, the range of pH 6.0 – 8.0, shows the most efficient removal for Copper was up to 95% and Zinc 97% by using SBR inoculated with activated sludge originated from palm oil mill pond. This suggests that biological method could be utilized to remove heavy metals from wastewaters. In addition, pH plays an important role when dealing with microorganism. A correct condition is necessary for the microorganism to fully optimized its activity.